The entrenchment of the ideal worker norm during the COVID-19 pandemic: Evidence from working mothers in the United States - Zanhour, Mona; Sumpter, Dana (Gender, Work and Organization, 2022)
We study shifts in the ideal worker culture as experienced by working mothers across organizations in the United States during the COVID-19 pandemic. Experiences of 53 interviewees who attended to increased responsibilities across both work and family domains revealed an entrenchment of the ideal worker culture across nearly all organizations and professions. This manifested in three levels: as (1) a reinforced ideal worker culture in the workplace through work intensification, increased competitiveness, and surface-level support; (2) the reinforcing of organizations' ideal worker norms at home, with gendered division of space and labor; and (3) experienced internalized ideal worker norms in the expectations working mothers maintained for themselves. These findings offer insight into the lives of working mothers during the COVID-19 pandemic and the challenges which have pushed many mothers to reduce work hours or leave the workforce. Highlighting the intricate nature of the entrenchment of the ideal worker culture informs implications for theory of gendered organizations and for organizational practice. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; culpabilité des mères; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail des mères; états-unis